Hälsokontrollen av den gemensamma jordbrukspolitiken (CAP) - Källman, Camilla (2009)
The Healthcheck is an evaluation of the 2003 years reform of the Common Agricultural Policy (CAP). When the Healthcheck of CAP is decided, most likely in the beginning of 2009, there will be a discussion about how CAP will appear in the next budget period 2013. One main question in the Healthcheck is how the farm support will be designed. A suggestion that has arised is if todays addition amount for dairy- and beef production should be transferred to the fundamental farm support. In this exam theses calculations has been done in created typical farms in every Swedish support region for cereals-, dairy- and beef production. Also calculations for horse farms that offers nature riding have been made. Personal deep interviews have been done with farmers in these different areas. This potential transfer to fundamental farm support does not benefit neither dairy- or beef production, whether the price level of 2007 or 2015 is used. If the expected price level of 2015 is used, dairy producers can get a reduced income between -15,4 to -39,2 %. Beef producers risk to get a reduced income between -30 to -38,9 %. One probable development if this transfer take place in year 2015 is that there could be fewer dairy- and beef producers in the southern part of Sweden. These farmers can instead change their production to cereal production. One development towards increase cereal production with larger farms would also result in more sparsely populated area between farms and therefore less population in the actual area. A development can take place that smaller farms are shut down and included into bigger unities. That does not benefit the desirable development for the countryside, which is the opposite . When it comes to cereals it should be mentioned that the prices were high in year 2007, and therefore there were higher incomes than usual for the cereal farmers. With consideration to the price level 2007 and what support region set in focus, the income for cereal farmers could vary between 1,9 – 12,7 %. Consider the hypothetical price level of 2015, TB 2 would decrease for all farmers except one. That is despite increased basic amount the fundamental farm support. Overall the cereal farmers would be the once that get more payments. Also horse farms benefits from a increase of the fundamental farm support. Although horse farms have lower land area, an increase in the fundamental farm support would be of big meaning for them according to the interviews in this study.